The American Law Institute A Centennial History - Gold, Andrew S.; Gordon, Robert W. (Oxford University Press, 2023)
This book collects together a series of original essays in honor of the American Law Institute's (ALI's) Centennial. The essays are authored by leading experts in their fields, often including current and former Restatement Reporters. The essays also provide a wide range of perspectives on both methodology and the law. The volume coverage focuses on specific ALI undertakings, including some of the more important Restatements and Codes; several leading Principles projects; statutory projects such as the Model Penal Code and the Uniform Commercial Code; themes that cut across substantive fields of law (such as Restatements and codification or Restatements and the common law); and the ALI's institutional history over the past century. The resulting book is a unique and compelling contribution to its fields of study.